A Retrospective Observational Study of the Impact of HIV Status on the Outcome of Paediatric Intensive Care Unit Admissions at a Tertiary Hospital in South Africa (2015-2019) - Kim Whitehead; Daynia E. Ballot (MDPI AG, 2023)
HIV-infected and HIV-exposed but uninfected (HEU) children have unique health risks. Our study looked at how HIV exposure and infection impact presentation and outcomes in PICU in an era of improved ART. A retrospective analysis of children admitted to PICU was performed. The sample was divided into HIV negative, HEU and HIV infected, and presentation and outcomes were compared with a significance level set at α = 0.05. Our study showed that 16% (109/678) of children admitted to PICU were HEU and 5.2% (35/678) were HIV infected. HIV-infected children were admitted at a younger age (median two months) with an increased incidence of lower respiratory infections than HIV-negative children (p < 0.001); they also required longer ventilation and admission (p < 0.001). HIV-infected children had a higher mortality (40%) (p = 0.02) than HIV-negative (22.7%) children; this difference was not significant when comparing only children with a non-surgical diagnosis (p = 0.273). HEU children had no significant difference in duration of ICU stay (p = 0.163), ventilation (p = 0.443) or mortality (p = 0.292) compared to HIV-negative children. In conclusion, HIV-infected children presented with more severe disease requiring longer ventilation and admission. HEU had similar outcomes to HIV-negative children.